The construct validity of a Belgian assessment centre: A comparison of different models - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2001)
This study investigates the construct validity of a Belgian assessment centre through a comprehensive set of confirmatory factor analysis models. In particular, the general confirmatory factor analysis approach as well as the correlated uniqueness approach are fitted to the same data. Results replicate Sagie and Magnezy's (1997) finding that the correlated uniqueness model is appropriate to represent exercise effects in assessment centres, as a good fit and no estimation problems are obtained. In this model the dimensions explain 36% of variance, revealing evidence of convergent validity. Possibly, this is due to the careful design of this assessment centre. Evidence of discriminant validity, however, is not established, as the dimension factors are highly correlated.